Dari William Seymour ke Misi Global: Warisan Pentakostal bagi Praktik Amanat Agung - Efri Mariana Luis; Jonathan Patrick Lumban Tobing; Meriyana Meriyana (Davar : Jurnal Teologi, 2026)
Abstract This study addresses a gap between historical studies of the Azusa Street revival and analyses of contemporary Pentecostal mission practice, which are often treated separately, leaving the conceptual relationship between early Pentecostal pneumatology and the global practice of the Great Commission insufficiently articulated. This study aims to examine the historical and theological continuity between William Seymour’s pneumatological vision and mission practice within global Pentecostalism. Employing a qualitative approach with a historical-theological design, the study analyzes primary sources from the early Pentecostal revival alongside contemporary literature on mission theology and pneumatology, interpreted through a hermeneutical framework within the perspective of missio Dei. The findings indicate that the outpouring of the Holy Spirit in early Pentecostalism was understood as a commissioning event that shaped the church as a participatory and cross-cultural missionary community, functioning as an operative principle in evangelistic patterns, lay mobilization, and social engagement. These findings suggest a conceptual continuity between Seymour’s pneumatology and the contemporary practice of the Great Commission in global contexts, albeit expressed in dynamic and contextual forms. Therefore, Pentecostal pneumatology may be understood as a significant theological framework for interpreting the transformation of contemporary mission paradigms.   Keywords: William Seymour; Azusa Street Revival; Pentecostal Pneumatology; Great Commission; Global Mission   Abstrak Penelitian ini berangkat dari kesenjangan antara kajian historis kebangunan Azusa Street dan analisis praksis misi Pentakostal kontemporer yang umumnya diperlakukan terpisah, sehingga hubungan konseptual antara pneumatologi awal dan praktik Amanat Agung global belum dijelaskan secara sistematis. Penelitian ini bertujuan menganalisis kesinambungan historis dan teologis antara visi pneumatologis William Seymour dan praktik misi dalam Pentakostalisme global. Penelitian menggunakan pendekatan kualitatif dengan desain historis-teologis melalui analisis terhadap sumber primer kebangunan awal serta literatur teologi misi dan pneumatologi kontemporer, yang diolah dengan kerangka hermeneutis dalam perspektif missio Dei. Hasil penelitian menunjukkan bahwa pencurahan Roh Kudus dalam tradisi Pentakostal awal dipahami sebagai peristiwa pengutusan yang membentuk gereja sebagai komunitas misioner partisipatif dan lintas budaya, serta berfungsi sebagai prinsip operatif dalam pola penginjilan, mobilisasi umat, dan keterlibatan sosial. Temuan ini mengindikasikan adanya kesinambungan konseptual antara pneumatologi Seymour dan praktik Amanat Agung dalam konteks global, meskipun diekspresikan dalam bentuk yang kontekstual dan dinamis. Oleh karena itu, pneumatologi Pentakostal dapat dipahami sebagai salah satu kerangka teologis penting dalam menjelaskan transformasi paradigma misi gereja kontemporer.   Kata Kunci: William Seymour; Azusa Street Revival; Pneumatologi Pentakostal; Amanat Agung; Misi Global